Boards and Cords: Discriminating Types of Artificial Cranial Deformation in Prehispanic South Central Andean Populations. (12th August 2011) - O'Brien, T. G.; Stanley, A. M.
ABSTRACT For over a century, a number of ambiguous typologies have been employed to distinctly categorise types of artificial cranial deformation. This paper provides a quantitative method, based on multiple dimensions and discriminant function analysis, by which to assign skulls not only into discrete categories: deformed or not, but also by type: annular or tabular. A series of prehispanic, adult, human crania (n = 469) from archaeological sites in Argentina, Bolivia, Chile and Peru represented by both normal and artificially deformed specimens, provide craniometric data for four measurements across the vault: maximum cranial length, breadth and height and the frontal chord. These data are used to develop three indices which in turn are used to compute two discriminant functions. Results are plotted on a territorial map whereby the type of deformity can be determined. When these methods were applied to a comparative cranial sample of nondeformed skulls from South America, 100% of the samples was found to be nondeformed. When these methods were applied to the samples which were subjectively classified a priori by the first author as nondeformed, 81.3% of the samples were found to be nondeformed. This study demonstrates the value of a more objective and quantitative method by which to classify artificial cranial deformation, and thus provides a new approach. Copyright © 2011 John Wiley & Sons, Ltd.